CONCEPTUALISATION AND FRAMEWORK DEVELOPMENT FOR WORKPLACE WELL-BEING: A LITERATURE REVIEW - SONEYE, ADEWALE ABDULWAHEED; SANI-SAMBO, HALIMAH (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
Workplace well-being has remained an evergreen concern in academic and professional fields. It has, however, suffered from the lack of a unified definition, with scholars, professionals, and policymakers bringing in diverse perspectives. This study reviews existing literature to contribute to the discourse on the conceptualisation of workplace well-being. The study adopts a qualitative approach, utilising thematic analysis. After applying specific criteria to eliminate literature that did not suit the study, the researchers selected 75 scholarly articles published between 2010 and 2024. The study reveals various terms and descriptors already used in the conceptualisation of workplace well-being fall into seven broad themes, which are psychological and emotional well-being, physical health and safety, job satisfaction and engagement, social relationships and support, life satisfaction and personal fulfilment, work-life balance and flexibility, and organisational commitment and performance. The study proposes a definition of workplace well-being that captures the thematic categorisations. This definition integrates theoretical perspectives, including the Job Demands-Resources (JD-R) model, psychological safety theory (PST), and ergonomic well-being. The study also proposes a framework emphasising the multi-dimensional attribute and the interplay between work and non-work environments. The definition and framework advanced in this study contribute to the ongoing discourse on this subject. These can serve as inputs into future research, developing organisational policies, and informing governmental regulations that enhance employee well-being and performance.